What Motivates People With (Pre)Diabetes to Move? Testing Self-Determination Theory in Rural Uganda - De Man, Jeroen; Wouters, Edwin; Absetz, Pilvikki; Daivadanam, Meena; Naggayi, Gloria; Kasujja, Francis Xavier; Remmen, Roy; Guwatudde, David; Van Olmen, Josefien (Frontiers in Psychology, 2020)
Introduction: Sub-Saharan Africa is experiencing a rapid growth of type 2 diabetes and its’ related burden. Regular physical activity is a successful prevention strategy, but is challenging to maintain. Self-determination theory posits that more autonomously motivated behavior is more sustainable. Evidence to support this claim is lacking in sub-Saharan Africa. This study aims to explore the relationships between latent constructs of autonomous and controlled motivation, perceived competence, perceived relatedness, physical activity behavior, and glycemic biomarkers. Methods: Structural equation modelling was applied to cross-sectional data from a rural Ugandan population (N = 712, pre-diabetes = 329, diabetes = 383). Outcome measures included self-reported moderate and vigorous physical activity, pedometer counts, fasting plasma glucose and glycated hemoglobin. Results: Our findings support self-determination theory, but also suggest that different types of motivation regulate different domains and intensities of physical activity. Higher frequency of vigorous physical activity – which was linked to a lower glycated hemoglobin and fasting plasma glucose – was predicted by autonomous motivation (β = .24) but not by controlled motivation (β = -0.05). However, we found no association with moderate physical activity frequency nor with pedometer counts. Perceived competence and perceived relatedness predicted autonomous motivation. Autonomous motivation functioned as a mediator between those needs and physical activity behavior. Conclusion: This is the first study providing evidence for a self-determination theory model explaining physical activity among people at risk of or living with type 2 diabetes in a rural sub-Saharan African setting. Our findings suggest that individuals who experience genuine support from friends or family and who feel competent in doing vigorous physical activity can become motivated through identification of health benefits of physical activity as their own goals. This type of motivation resulted in a higher frequency of vigorous physical activity and better glycemic biomarkers. On the other hand, people who felt more motivated through pressure from others or through feelings of guilt or shame were not more engaged in physical activity. Trial registration: ISRCTN 11913581. Registered 10 January 2017.